Financial Statement Accountability of BAZNAS Bukittinggi City According to PSAK 45 - Khalila Husnasari; Rizky Arvi Yunita; Ervina Rosarina Hasibuan (Al-Mal: Jurnal Akuntansi dan Keuangan Islam, 2025)
This study examines the accountability of the financial statements of BAZNAS Bukittinggi City, as accountability is a crucial aspect of financial reporting in organizations and institutions. Using a mixed-method approach, the research collected data through questionnaires and interviews with 100 randomly selected muzakki (donors). The findings indicate that the accountability of BAZNAS Bukittinggi City's financial reports is categorized as good based on the six selected indicators. Interviews with BAZNAS employees revealed that financial reports are prepared periodically in written form and disseminated through mass media and social media. However, for elderly donors, reports are distributed in hardcopy format, which is less efficient and affects the timeliness of reporting, thereby influencing accountability. Additionally, the public's limited understanding of financial reports further hinders transparency. Due to research limitations, this study focused on six accountability indicators. Future research is recommended to explore financial report accountability and management information systems more comprehensively, incorporating additional relevant factors.